A Numerical Study on Gas Mixing Time in a Low-Pressure (Driven) Section of a Shock Tube - YuanGang Wang(왕위엔강); Cheon Hyeon Cho(조천현); Chae Hoon Sohn(손채훈); Youngbin Yoon(윤영빈) (한국연소학회지, 2017)
The fuel and oxidizer mixing process in the shock tube driven section is simulated numerically. The boundary condition is set based on an shock tube experimental condition. The objective is to predict the gas mixing time for experiments. In the experiment, the amount of fuel to be injected is determined in advance. Then, according to duration of fuel injection, 5 cases with the same fuel mass but different fuel mass flow rate are simulated. After fuel is injected into the driven section, the fuel and air will be mixed with each other through convection and diffusion processes. The mixing time is predicted numerically for experiments. KCI Citation Count: 0